Prevalence of faecal carriage of extended‐spectrum β‐lactamase (ESBL)‐producing Escherichia coli in veterinary hospital staff and students. Issue 1 (7th January 2019) - Royden, Alexandra; Ormandy, Emma; Pinchbeck, Gina; Pascoe, Ben; Hitchings, Matthew D; Sheppard, Samuel K; Williams, Nicola J
Abstract : Extended‐spectrum β‐lactamase (ESBL)‐producing bacteria causing clinical infections are often also multidrug‐resistant (MDR; resistance to ≥3 antimicrobial drug classes), therefore treatment options may be limited. High carriage rates of these potentially zoonotic bacteria have been found in livestock and companion animals. Therefore, people working in veterinary hospitals may be a high‐risk population for carriage. This is the first study to determine the prevalence and longitudinal carriage of antimicrobial‐resistant (AMR) and ESBL‐producing faecal Escherichia coli in veterinary hospital staff and students. Prevalence of faecal AMR and ESBL‐producing E coli was determined in 84 staff members and students in three UK veterinary hospitals. Twenty‐seven participants were followed for six weeks to investigate longitudinal carriage. Antimicrobial susceptibility and phenotypic ESBL production were determined and selected isolates were whole genome sequenced. ESBL‐producing E coli were isolated from five participants (5.95 per cent; 95 per cent CI 0.89 to 11.0 per cent); two participants carried ESBL‐producing E coli resistant to all antimicrobials tested. Carriage of MDR E coli was common (32.1 per cent; 95per cent CI 22.2 to 42.1 per cent) and there was a high prevalence of ciprofloxacin resistance (11.9 per cent; 95 per cent CI 4.98 to 18.8 per cent). ESBL‐producing E coli were isolated from seven longitudinal participants (25.9 per cent; 95 per cent CI 9.40 to 42.5 per cent); two participants carried ESBL‐producing E coli for the entire study period. Twenty‐six participants (96.3 per cent; 95 per cent CI 89.2 to 100) carried ≥1 MDR E coli isolate during the six‐week period, with seven participants (25.9 per cent) carrying ≥1 MDR isolate for at least five out of six weeks. The prevalence of faecal ESBL‐producing E coli in cross‐sectional participants is similar to asymptomatic general populations. However, much higher levels of carriage were observed longitudinally in participants. It is vital that veterinary hospitals implement gold‐standard biosecurity to prevent transmission of MDR and ESBL‐producing bacteria between patients and staff. Healthcare providers should be made aware that people working in veterinary hospitals are a high‐risk population for carriage of MDR and ESBL‐producing bacteria, and that this poses a risk to the carrier and for transmission of resistance throughout the wider community.